Graphite silicon carbide composite bearing and preparation method thereof

The porous graphite skeleton blank is prepared by selective laser sintering technology, and a three-dimensional network structure of graphite and silicon carbide is formed in combination with high-temperature melt-silicon seepage technology, which solves the problem of difficulty in controlling graphite content and pore structure in the existing technology, and achieves the good self-lubricating and mechanical properties of graphite silicon carbide composite bearings.

CN119775009APending Publication Date: 2025-04-08CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411893561.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing graphite silicon carbide composite bearing preparation process is difficult to control the graphite content and its distribution state, as well as the size, shape and distribution state of pores in the porous graphite skeleton prefabricated body, making it difficult to achieve the purpose of ensuring good self-lubricating effect and improving mechanical properties.

Method used

Selective laser sintering technology is used to quickly prepare porous graphite skeleton blanks, and their strength and density are improved through secondary curing, vacuum pressure immersion and carbonization treatment. Then, the porous graphite skeleton preform is embedded with high-purity silicon powder and boron carbide powder, and the high-temperature melt-infiltrating silicon is carried out, so that the high-purity silicon powder and the resin carbon in the porous graphite skeleton preform undergo in situ sintering reaction, forming a stable silicon carbide, forming a three-dimensional continuous interpenetrating network structure between graphite and silicon carbide.

Benefits of technology

It realizes the good self-lubricating effect and improves mechanical properties of graphite silicon carbide composite bearings, and is suitable for industrial applications with high speed heavy loads and high and low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775009A_ABST
    Figure CN119775009A_ABST
Patent Text Reader

Abstract

The invention discloses a graphite silicon carbide composite bearing and a preparation method thereof, the graphite silicon carbide composite bearing is formed by compounding a porous graphite skeleton preform and silicon carbide, and graphite and silicon carbide are compounded to form a three-dimensional continuous interpenetrating network structure by adjusting the content of mesocarbon microbeads. The preparation method of the graphite silicon carbide composite bearing comprises the process links of mixed powder preparation, porous graphite skeleton biscuit forming, secondary curing, vacuum pressure impregnation, carbonization, high-temperature melting siliconizing, grinding machining and the like. The preparation method provided by the invention has the advantages of short process flow, high production efficiency, low cost and the like, and the prepared graphite silicon carbide composite bearing has the advantages of wear resistance, high bearing capacity, good lubricating effect and the like, and is suitable for high-speed heavy-load and high-low-temperature industrial application occasions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphite silicon carbide composite bearing and a preparation method thereof, belonging to the technical field of non-metallic material forming and engineering application thereof, and specifically to a rapid manufacturing method of a graphite silicon carbide composite bearing, which is used as a self-lubricating part in a working environment of high speed, heavy load and large temperature difference. Background Art

[0002] With the rapid development of modern industrial technology, the requirements for comprehensive performance of bearings are increasing day by day in order to adapt to high speed, high and low temperature, high load and corrosive environment. Traditional bearing materials such as metal alloys (steel, copper alloy, aluminum alloy), plastic materials (polytetrafluoroethylene, nylon, polyoxymethylene), ceramic materials (aluminum oxide, silicon nitride, silicon carbide), etc., are prone to problems such as increased wear, lubrication failure, and reduced dimensional stability due to thermal expansion under these extreme conditions.

[0003] Graphite bearings have good self-lubrication, low friction coefficient and good thermal conductivity due to the special crystal structure of graphite, but graphite has a high thermal expansion coefficient, and its mechanical strength and wear resistance are relatively poor. In terms of microstructure, when graphite is subjected to shear or impact loads, interlayer separation is prone to occur, which accelerates wear; when the thermal expansion of the bearing edge and stress concentration area is uneven, the accumulation of thermal stress will cause the formation and expansion of cracks, affecting the stability and life of the bearing. Pure silicon carbide bearings have the problem of insufficient self-lubrication performance in practical applications, especially in environments without lubricating oil or with poor lubrication conditions. The friction coefficient is large (0.4~0.8), and some debris particles will be generated during friction. These debris particles will cause abrasive wear on the friction end surface, resulting in increased wear. In terms of microstructure, the grain boundaries of silicon carbide are weak, which makes the bearing more prone to fatigue fracture when subjected to repeated loads, which means that pure silicon carbide bearings are prone to crack expansion or even fracture when subjected to impact or stress concentration.

[0004] Compounding graphite and silicon carbide in a certain way to form a graphite silicon carbide composite material can fully utilize the advantages of both and make up for their respective shortcomings. At present, the common preparation methods of graphite and silicon carbide composite materials are mainly powder metallurgy and graphite matrix infiltration. The former is based on the preparation of graphite silicon carbide mixed powder, and adopts pressing and high-temperature sintering to first obtain graphite silicon carbide ceramic composite materials, and then obtain graphite silicon carbide composite bearings through mechanical cutting. The latter is to use vacuum pressure infiltration technology to "introduce" high-purity silicon powder into the internal pores of the graphite matrix, thereby obtaining a graphite silicon carbide composite material, and then obtain a graphite silicon carbide composite bearing through mechanical cutting. The former cannot accurately control the distribution state of ceramic powder in graphite powder. This leads to poor stability of the composite material. The pore state of the graphite matrix directly affects the amount of silicon liquid infiltration. At the same time, the continuous reaction of silicon carbide ceramics hinders the subsequent entry of silicon liquid, so the infiltration depth is small, and silicon carbide and graphite matrix are mostly surface composites. In recent years, Zhejiang University has proposed that continuous pore formation on the silicon carbide matrix can greatly reduce the friction coefficient. However, the bending strength of the silicon carbide ceramic matrix has decreased significantly (the lowest is only 185MPa). Compounding fluorinated graphite can better guarantee the mechanical properties of the ceramic matrix, but the friction coefficient is high.

[0005] In summary, it is difficult to control the graphite content and its distribution state in the existing preparation process of graphite silicon carbide composite bearings, as well as the size, shape and distribution state of the pores in the porous graphite skeleton preform. There is currently a lack of effective process methods to achieve the purpose of ensuring good self-lubricating effect and improving the mechanical properties of graphite silicon carbide composite bearings. Summary of the invention

[0006] The present invention provides a graphite silicon carbide composite bearing and a preparation method thereof, and the basic process is as follows: First, a porous graphite skeleton blank is quickly prepared by using selective laser sintering technology on the basis of the preparation of mixed powder. Secondly, since the porous graphite skeleton blank has a high porosity and poor mechanical properties, it is subjected to secondary curing, vacuum pressure impregnation and carbonization treatment to obtain a porous graphite skeleton preform with a certain strength and a high open porosity. Then, the porous graphite skeleton preform is embedded with high-purity silicon powder and boron carbide powder and placed in a graphite crucible, and then the graphite crucible is covered with a lid and placed in a vacuum sintering furnace. Through high-temperature melting and siliconization, the high-purity silicon powder and the resin carbon in the porous graphite skeleton preform undergo an in-situ sintering reaction to compound silicon carbide therein. Finally, the graphite silicon carbide composite bearing blank is ground to ensure the dimensional accuracy, structural accuracy and surface quality of the graphite silicon carbide composite bearing. The specific process flow is as follows: Figure 1 shown.

[0007] The following technical measures are taken to achieve the purpose of the invention: (1) By adjusting the content of each powder in the mixed powder and the parameters of each process in the preparation process, not only the graphite content in the bearing is increased, but also the mixing efficiency is improved, the adhesion and stability of the mixed powder during laser sintering are enhanced, and the mutual balance of various properties of the graphite silicon carbide composite bearing is achieved.

[0008] (2) The porous graphite skeleton blank is obtained by selective laser sintering (SLS) technology. The pore structure in the porous graphite skeleton blank is controllably adjusted by adjusting the laser process parameters, which provides an ideal pore structure for subsequent vacuum pressure impregnation and high-temperature melt siliconization, thereby improving the density and mechanical properties of the bearing.

[0009] (3) The mixed powder formula contains mesophase carbon microsphere powder (MCMB), which helps to improve the compatibility and dispersibility of the components in the mixed powder, thereby improving the overall sintering performance of the mixed powder. The mesophase carbon microsphere powder undergoes a self-shrinkage reaction after carbonization, which can reduce the porosity and increase the density and thermal conductivity of the porous graphite skeleton blank.

[0010] (4) After the porous graphite skeleton preform is embedded with high-purity silicon powder and boron carbide powder, it is placed in a vacuum sintering furnace. Stable silicon carbide is generated through high-temperature melt infiltration. The graphite and silicon carbide are composited to form a three-dimensional continuous interpenetrating network structure, which not only enhances the mechanical properties of the bearing, but also reduces the friction coefficient of the bearing, achieving a good self-lubricating effect.

[0011] The method provided by the present invention not only rapidly prepares graphite silicon carbide composite bearings, but also studies the influence of the content of mesophase carbon microsphere powder on the various properties of graphite silicon carbide composite bearings, thereby achieving controllable regulation of various properties of graphite silicon carbide composite bearings. Compared with traditional manufacturing processes, the production process of this method is relatively simple, and has the characteristics of rapidity, high efficiency, and low cost, and is suitable for large-scale production. The prepared graphite silicon carbide composite bearings have the advantages of wear resistance, strong load-bearing capacity, and good lubrication effect, and are suitable for high-speed, heavy-load, and high-low temperature industrial applications.

[0012] A graphite silicon carbide composite bearing and a preparation method thereof include the following specific steps: (1) Preparation of mixed powder: Graphite powder, mesophase carbon microsphere powder, thermosetting phenolic resin powder and high-purity silicon powder are mixed to obtain a mixed powder; (2) Forming a porous graphite skeleton blank: The mixed powder is subjected to selective laser sintering molding technology to obtain a porous graphite skeleton blank by 3D printing; (3) Secondary curing: heating the porous graphite skeleton blank for secondary curing to improve the bending strength of the porous graphite skeleton blank; (4) Vacuum pressure impregnation: The porous graphite skeleton blank after secondary curing is subjected to vacuum pressure impregnation to improve the density of the porous graphite skeleton blank; (5) Carbonization: Carbonizing the porous graphite skeleton blank under nitrogen protection to obtain a porous graphite skeleton preform; (6) High-temperature melt siliconization: After the porous graphite skeleton preform is embedded with high-purity silicon powder and boron carbide powder, high-temperature melt siliconization is carried out under vacuum and heating conditions to obtain a graphite silicon carbide composite bearing blank; (7) Grinding: Grinding the graphite silicon carbide composite bearing to obtain a graphite silicon carbide composite bearing.

[0013] Preferably, the mixed powder preparation process in step (1) is as follows: first, a proper amount of graphite powder, mesophase carbon microsphere powder, thermosetting phenolic resin powder, high-purity silicon powder and phenolic resin solution are uniformly mixed; secondly, the ethanol solution is removed by hot air drying, and the mixed powder is crushed; finally, the crushed mixed powder is sieved to obtain a mixed powder with a certain particle size distribution range.

[0014] The powder formula for preparing the mixed powder in step (1) is as follows: the mass proportion of graphite powder is 30wt%~50wt%, and the particle size is 150 mesh~500 mesh; the mass proportion of mesophase carbon microsphere powder is 10wt%~40wt%, and the particle size is 150 mesh~500 mesh; the mass proportion of thermosetting phenolic resin powder is 20wt%~30wt%, and the particle size is 200 mesh~1000 mesh; the mass proportion of high-purity silicon powder is 5wt%~10wt%, and the particle size is 200 mesh~1000 mesh.

[0015] In some embodiments, the mixing process in step (1) is as follows: a powder formula for preparing a mixed powder, a phenolic resin solution (density 1.2 g / cm 3 , mass fraction of 40%, viscosity of 600mpa~1500mpa) and ethanol solution (density of 0.789g / cm 3 ~0.791g / cm 3 , mass fraction of 99.7%) are added into a mixer in a ratio of 7:3:9, and the mixing time is 1h~2h; then, the mixed powder is placed in a hot air drying oven, the drying temperature is 60℃~90℃, and the drying time is 1h~2h; then, the dried powder is poured into a crusher, the rotation speed is 30000~32000r / min, and the crushing time is 5min~8min; finally, the crushed powder is poured into a 150-mesh sieve for sieving, the undersize is taken, and then poured into a 1000-mesh sieve for sieving, the oversize is taken, the mixed powder particle size distribution is between 150 mesh and 1000 mesh, and the mixed powder for preparing a porous graphite skeleton blank is obtained.

[0016] Preferably, the selective laser sintering forming technology is carried out in a selective laser sintering forming equipment.

[0017] The selective laser sintering process parameters are: preheating temperature 40℃~45℃; laser power 17W~21W; scanning rate 1000mm·s -1 ~2000mm·s -1 ; The scanning interval is 0.05mm~0.1mm; the layer thickness is 0.1mm~0.2mm, and a porous graphite skeleton blank is obtained.

[0018] Preferably, the secondary curing process in step (3) is as follows: placing the porous graphite skeleton blank into a curing furnace at a temperature of 160° C. to 180° C. for a holding time of 0.5 h to 1 h.

[0019] Preferably, the vacuum pressure impregnation process in step (4) is as follows: placing the porous graphite skeleton blank into a vacuum pressure impregnation furnace, evacuating the vacuum to below -0.1 MPa, and then introducing liquid phenolic resin (density 1.2 g / cm 3 , mass fraction of 40%, viscosity of 600mpa~1500mpa) as the impregnating agent to completely immerse the porous graphite skeleton blank, then fill with nitrogen and pressurize to 0.3MPa~0.5MPa, at the same time, heat the outer jacket of the vacuum pressure impregnation furnace to 150℃~160℃, heat the inner temperature of the impregnation kettle to 90℃~100℃, and the impregnation time is 0.25h~0.5h.

[0020] Preferably, the carbonization process in step (5) is as follows: placing the impregnated porous graphite skeleton blank into a vacuum carbonization furnace, evacuating the vacuum to below -0.2 MPa, then introducing inert gas nitrogen, and performing temperature carbonization. The first stage is 30°C~200°C, and the heating rate is 50-100°C / h; the second stage is 200°C~600°C, and the heating rate is 30-60°C / h; the third stage is heating to 800°C at a heating rate of 100-150°C / h, and the heat preservation time is 1-2h, and then cooling to room temperature with the furnace and taking out to obtain a porous graphite skeleton preform.

[0021] In the above-mentioned temperature increase conditions, 30°C~200°C refers to a temperature increase from 30°C to 200°C; 200°C~600°C refers to a temperature increase from 200°C to 600°C.

[0022] Preferably, in step (6), the mass ratio of high-purity silicon powder to boron carbide powder is 10-15:1.

[0023] Among them, the particle size of high-purity silicon powder is 200 mesh ~ 1000 mesh, and the purity is 99.5%; the particle size of boron carbide powder is 200 mesh ~ 1000 mesh.

[0024] In some embodiments, the high temperature melt siliconizing is performed in a graphite crucible.

[0025] In the high-temperature melt siliconization step, the vacuum degree is evacuated to below -0.1MPa, and the temperature is increased for high-temperature melt infiltration. The first stage is 30℃~1400℃, and the heating rate is 200-400℃ / h; the second stage is 1500℃~1600℃, and the heating rate is 50-100℃ / h; the insulation time is 1h~2h, and then it is cooled to room temperature and taken out to obtain a graphite silicon carbide composite bearing blank.

[0026] In the above-mentioned temperature rising conditions, 30°C~1400°C refers to the temperature rising from 30°C to 1400°C; 1500°C~1600°C refers to the temperature rising from 1500°C to 1600°C.

[0027] The grinding process in step (7) is to grind the graphite silicon carbide composite bearing blank using a grinding wheel with a rotation speed of 150 r / min to 200 r / min, a particle size of 200 mesh to 300 mesh, and a hardness of K grade, so as to ensure the dimensional accuracy, structural accuracy and surface quality of the graphite silicon carbide composite bearing.

[0028] The above technical method has the following advantages: 1. The present invention adopts a wet mixing process to evenly mix a variety of powders, and obtains a mixed powder for preparing a porous graphite skeleton blank through the steps of mixing, grinding, drying, crushing, screening, etc. The components in the mixed powder are evenly distributed, which helps the smooth progress of subsequent processes and ensures the quality of the graphite silicon carbide composite bearings, thereby achieving a mutual balance of various properties of the graphite silicon carbide composite bearings.

[0029] 2. The present invention uses selective laser sintering technology to quickly prepare porous graphite skeleton blanks, which can produce any complex bearing geometry and internal structure. No support structure is required during the preparation process, which simplifies the forming process and improves material utilization and production efficiency.

[0030] 3. The present invention improves the strength and density of the porous graphite skeleton blank through the process steps of secondary curing, vacuum pressure impregnation, carbonization, etc., and obtains a porous graphite skeleton preform. By accurately controlling the process parameters of each step, the controllable adjustment of the bearing structure and performance is achieved.

[0031] 4. The present invention uses high-temperature molten siliconization to cause an in-situ sintering reaction between high-purity silicon powder and resin carbon in a porous graphite skeleton preform to generate stable silicon carbide. The graphite and silicon carbide are composited to form a three-dimensional continuous interpenetrating network structure, which not only improves the mechanical properties and self-lubricating properties of the bearing, but also enhances its high temperature resistance, corrosion resistance, thermal conductivity and thermal stability, so that the bearing can operate stably in harsh working environments, meeting the needs of industrial applications under harsh working conditions.

[0032] The graphite silicon carbide composite bearing prepared by the preparation method of the present invention has a Vickers hardness of 4.1-5.4 GPa and a wear rate of 1.20×10 -6 ~3.85×10 -6 mm 3 / Nm; friction coefficient 0.15~0.3; thermal expansion coefficient 3.0×10 -6 ~5.0×10 -6 Under the condition of m / k, the density is 2.5~3.2g / cm 3; Flexural strength 190~320 MPa; Compressive strength 350~420MPa; Thermal conductivity 140~170W / m·k. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a flow chart for preparing graphite silicon carbide composite bearings.

[0034] Figure 2 This is a three-dimensional model of a graphite silicon carbide composite bearing, A is the main view and B is the top view.

[0035] Figure 3 This is a picture of the porous graphite skeleton preform after carbonization.

[0036] Figure 4 This is a graphite silicon carbide composite bearing obtained by high temperature molten siliconization. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments: This implementation example is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following implementation examples.

[0038] Example 1 The powder formula for preparing the mixed powder in this embodiment is: graphite powder accounts for 50wt% by mass, and the particle size is 150 mesh ~ 500 mesh; mesophase carbon microsphere powder accounts for 10wt% by mass, and the particle size is 150 mesh ~ 500 mesh; thermosetting phenolic resin powder accounts for 30wt% by mass, and the particle size is 200 mesh ~ 1000 mesh; high-purity silicon powder accounts for 10wt% by mass, and the particle size is 200 mesh ~ 1000 mesh.

[0039] The process for preparing the mixed powder in this example is as follows: first, the powder formula and the phenolic resin solution (density 1.2 g / cm 3 , mass fraction of 40%, viscosity of 600mpa~1500mpa) and ethanol solution (density of 0.789g / cm 3 ~0.791g / cm 3 , mass fraction of 99.7%) are added into a mixer in a ratio of 7:3:9, and the mixing time is 1 hour; then, the mixed powder is placed in a hot air drying oven, the drying temperature is 60°C, and the drying time is 1 hour; then, the dried powder is poured into a crusher, the rotation speed is 32000r / min, and the crushing time is 5min; finally, the crushed powder is poured into a 150-mesh sieve for sieving, the undersize is taken, and then poured into a 1000-mesh sieve for sieving, the oversize is taken, and the particle size distribution of the mixed powder is between 150 mesh and 1000 mesh, and the mixed powder for preparing a porous graphite skeleton blank is obtained.

[0040] In this embodiment, the selective laser sintering technology is used to quickly prepare porous graphite skeleton blanks. The specific process parameters are: preheating temperature is 40°C; laser power is 19W; scanning rate is 1000 ; The scanning interval is 0.1mm; the layer thickness is 0.2mm, and a porous graphite skeleton blank is obtained.

[0041] In this embodiment, the porous graphite skeleton blank is placed in a curing furnace at a temperature of 180°C and kept at a temperature for 0.5h to 1h. The porous graphite skeleton blank after secondary curing is placed in a vacuum pressure impregnation furnace, the vacuum degree is evacuated to below -0.1MPa, and then liquid phenolic resin is introduced as an impregnating agent (density 1.2g / cm 3 , mass fraction of 40%, viscosity of 600mpa~1500mpa), so that the porous graphite skeleton blank is completely immersed, and then filled with nitrogen and pressurized to 0.5MPa, and at the same time, the outer jacket of the vacuum pressure impregnation furnace is heated to 160℃, and the temperature in the impregnation kettle is raised to 100℃, and the impregnation time is 0.25h. The impregnated porous graphite skeleton blank is placed in a vacuum carbonization furnace, the vacuum degree is evacuated to below -0.2MPa, and then inert gas nitrogen is introduced for heating and carbonization. The first stage: 30℃~200℃, the heating rate is 100℃ / h; the second stage: 200℃~600℃, the heating rate is 60℃ / h; the third stage: the temperature is raised to 800℃ at a rate of 150℃ / h, the insulation time is 1h, and then it is cooled to room temperature with the furnace and taken out to obtain a porous graphite skeleton preform, such as Figure 3 shown.

[0042] In this embodiment, the porous graphite skeleton preform is embedded with high-purity silicon powder and boron carbide powder and placed in a graphite crucible, and then the graphite crucible is covered with a lid and placed in a vacuum sintering furnace, and then subjected to high-temperature melt siliconization. The high-temperature melt siliconization process is as follows: first, high-purity silicon powder (particle size of 200 mesh to 1000 mesh, purity of 99.5%) and boron carbide powder (particle size of 200 mesh to 1000 mesh) are mixed in a mass ratio of 10:1 to obtain a mixed powder; secondly, the porous graphite skeleton preform is embedded with the mixed powder and placed in a graphite crucible, and then the graphite crucible is covered with a lid and placed in a vacuum sintering furnace. Then, the vacuum degree is evacuated to below -0.1MPa, and the temperature is increased for high-temperature infiltration. The first stage is 30℃~1400℃, and the heating rate is 400℃ / h; the second stage is 1400℃~1600℃, and the heating rate is 50℃ / h; the heat preservation time is 1h, and then the furnace is cooled to room temperature and taken out to obtain a graphite silicon carbide composite bearing blank, such as Figure 4 shown.

[0043] In this embodiment, a grinding wheel with a rotation speed of 150 r / min, a particle size of 200 meshes, and a hardness of K grade is used to grind the graphite silicon carbide composite bearing blank to ensure the dimensional accuracy, structural accuracy and surface quality of the graphite silicon carbide composite bearing.

[0044] The experimental results show that the density of the prepared graphite silicon carbide composite bearing is 2.8g / cm 3 , flexural strength 220 , compressive strength 372 , Vickers hardness 4.7GPa, wear rate 2.7×10 -6 mm 3 / Nm, friction coefficient 0.2, thermal expansion coefficient 4.0×10 -6 m / k, thermal conductivity 148W / m·k.

[0045] Example 2 The powder formula for preparing the mixed powder in this embodiment is as follows: the mass of graphite powder accounts for 40wt%, and the particle size is 150 mesh ~ 500 mesh; the mass of mesophase carbon microsphere powder accounts for 20wt%, and the particle size is 150 mesh ~ 500 mesh; the mass of thermosetting phenolic resin powder accounts for 30wt%, and the particle size is 200 mesh ~ 1000 mesh; the mass of high-purity silicon powder accounts for 10wt%, and the particle size is 200 mesh ~ 1000 mesh.

[0046] The method steps are the same as those in Example 1.

[0047] The experimental results show that the density of the prepared graphite silicon carbide composite bearing is 3.2g / cm 3 , flexural strength 260 MPa, compressive strength 385 MPa, Vickers hardness 4.9 GPa, wear rate 1.2×10 -6 mm 3 / Nm, friction coefficient 0.15, thermal expansion coefficient 3.0×10 -6 m / k, thermal conductivity 170W / m·k.

[0048] Example 3 The powder formula for preparing the mixed powder in this embodiment is as follows: the mass of graphite powder accounts for 40wt%, and the particle size is 150 mesh ~ 500 mesh; the mass of mesophase carbon microsphere powder accounts for 30wt%, and the particle size is 150 mesh ~ 500 mesh; the mass of thermosetting phenolic resin powder accounts for 20wt%, and the particle size is 200 mesh ~ 1000 mesh; the mass of high-purity silicon powder accounts for 10wt%, and the particle size is 200 mesh ~ 1000 mesh.

[0049] The method steps are the same as those in Example 1.

[0050] The experimental results show that the density of the prepared graphite silicon carbide composite bearing is 2.9g / cm 3, flexural strength 305 MPa, compressive strength 406 MPa, Vickers hardness 5.4 GPa, wear rate 2.10×10 -6 mm 3 / Nm, friction coefficient 0.25, thermal expansion coefficient 3.5×10 -6 m / k, thermal conductivity 155W / m·k.

[0051] Example 4 The powder formula for preparing the mixed powder in this embodiment is as follows: the mass of graphite powder accounts for 30wt%, and the particle size is 150 mesh ~ 500 mesh; the mass of mesophase carbon microsphere powder accounts for 40wt%, and the particle size is 150 mesh ~ 500 mesh; the mass of thermosetting phenolic resin powder accounts for 20wt%, and the particle size is 200 mesh ~ 1000 mesh; the mass of high-purity silicon powder accounts for 10wt%, and the particle size is 200 mesh ~ 1000 mesh.

[0052] The method steps are the same as those in Example 1.

[0053] The experimental results show that the density of the prepared graphite silicon carbide composite bearing is 2.5g / cm 3 , flexural strength 190 MPa, compressive strength 353 MPa, Vickers hardness 4.1 GPa, wear rate 3.85×10 -6 mm 3 / Nm, friction coefficient 0.3, thermal expansion coefficient 5.0×10 -6 m / k, thermal conductivity 140W / m·k.

[0054] Example 5 The method steps are the same as those in Example 1, except that in the step of preparing the mixed powder, the mass percentage of the mesocarbon microsphere powder is 5 wt %.

[0055] The experimental results show that the density of the prepared graphite silicon carbide composite bearing is 2.6g / cm 3 , flexural strength 186 MPa, compressive strength 342 MPa, Vickers hardness 3.9 GPa, wear rate 3.9×10 -6 mm 3 / Nm, friction coefficient 0.32, thermal expansion coefficient 5.2×10 -6 m / k, thermal conductivity 131W / m·k.

[0056] Example 6 The method steps are the same as those of Example 1, except that the high temperature melt siliconizing step does not contain boron carbide powder.

[0057] The experimental results show that the density of the prepared graphite silicon carbide composite bearing is 2.71g / cm 3 , flexural strength 210 MPa, compressive strength 368 MPa, Vickers hardness 4.62 GPa, wear rate 2.73×10-6 mm 3 / Nm, friction coefficient 0.24, thermal expansion coefficient 4.2×10 -6 m / k, thermal conductivity 146W / m·k.

Claims

1. A method for preparing a graphite silicon carbide composite bearing, characterized in that: The steps include: (1) Preparation of mixed powder: Graphite powder, mesophase carbon microsphere powder, thermosetting phenolic resin powder and high-purity silicon powder are mixed to obtain a mixed powder; (2) Forming a porous graphite skeleton blank: The mixed powder is subjected to selective laser sintering molding technology to obtain a porous graphite skeleton blank by 3D printing; (3) Secondary curing: heating the porous graphite skeleton blank for secondary curing to improve the bending strength of the porous graphite skeleton blank; (4) Vacuum pressure impregnation: The porous graphite skeleton blank after secondary curing is subjected to vacuum pressure impregnation to improve the density of the porous graphite skeleton blank; (5) Carbonization: Carbonizing the porous graphite skeleton blank under nitrogen protection to obtain a porous graphite skeleton preform; (6) High-temperature melt siliconization: After the porous graphite skeleton preform is embedded with high-purity silicon powder and boron carbide powder, high-temperature melt siliconization is carried out under vacuum and heating conditions to obtain a graphite silicon carbide composite bearing blank; (7) Grinding: Grinding the graphite silicon carbide composite bearing to obtain a graphite silicon carbide composite bearing.

2. The method for preparing a graphite silicon carbide composite bearing according to claim 1, characterized in that: The powder formula for preparing the mixed powder in step (1) is as follows: the mass proportion of graphite powder is 30wt%~50wt%, and the particle size is 150 mesh~500 mesh; the mass proportion of mesophase carbon microsphere powder is 10wt%~40wt%, and the particle size is 150 mesh~500 mesh; the mass proportion of thermosetting phenolic resin powder is 20wt%~30wt%, and the particle size is 200 mesh~1000 mesh; the mass proportion of high-purity silicon powder is 5wt%~10wt%, and the particle size is 200 mesh~1000 mesh.

3. The method for preparing a graphite silicon carbide composite bearing according to claim 1, characterized in that: The selective laser sintering process parameters in step (2) are: preheating temperature of 40°C to 45°C; laser power of 17W to 21W; scanning rate of 1000mm·s -1 ~2000mm·s -1 ; The scanning interval is 0.05mm~0.1mm; the layer thickness is 0.1mm~0.2mm, and a porous graphite skeleton blank is obtained.

4. The method for preparing a graphite silicon carbide composite bearing according to claim 1, characterized in that: The secondary curing process in step (3) is as follows: placing the porous graphite skeleton blank into a curing furnace at a temperature of 160° C. to 180° C. for a holding time of 0.5 h to 1 h.

5. The method for preparing a graphite silicon carbide composite bearing according to claim 1, characterized in that: The vacuum pressure impregnation process in step (4) is as follows: placing the porous graphite skeleton blank into a vacuum pressure impregnation furnace and evacuating the vacuum to -0.1 Next, liquid phenolic resin is introduced as an impregnating agent to completely immerse the porous graphite skeleton blank, and then nitrogen is filled and pressurized to 0.3MPa~0.5MPa. At the same time, the outer jacket of the vacuum pressure impregnation furnace is heated to 150℃~160℃, and the temperature in the impregnation kettle is raised to 90℃~100℃. The impregnation time is 0.25h~0.5h.

6. The method for preparing a graphite silicon carbide composite bearing according to claim 1, characterized in that: The carbonization process in step (5) is as follows: placing the impregnated porous graphite skeleton blank into a vacuum carbonization furnace, evacuating the vacuum to below -0.2 MPa, then introducing inert gas nitrogen, and performing temperature carbonization. The first stage is 30°C to 200°C, and the heating rate is 50-100°C / h; the second stage is 200°C to 600°C, and the heating rate is 30-60°C / h; the third stage is heating to 800°C at a heating rate of 100-150°C / h, and the heat preservation time is 1-2h, and then cooling to room temperature with the furnace and taking out to obtain a porous graphite skeleton preform.

7. The method for preparing a graphite silicon carbide composite bearing according to claim 1, characterized in that: In the step (6), the mass ratio of high-purity silicon powder to boron carbide powder is 10-15:

1.

8. The method for preparing a graphite silicon carbide composite bearing according to claim 7, characterized in that: In step (6), the vacuum degree is evacuated to below -0.1 MPa, and the temperature is raised to perform high-temperature infiltration. The first stage: 30℃~1400℃, the heating rate is 200-400℃ / h; the second stage: 1400℃~1600℃, the heating rate is 50-100℃ / h; the insulation time is 1h~2h, then cooled to room temperature and taken out to obtain a graphite silicon carbide composite bearing blank.

9. The method for preparing a graphite silicon carbide composite bearing according to claim 1, characterized in that: The grinding process in step (7) is as follows: grinding the graphite silicon carbide composite bearing blank using a grinding wheel with a rotation speed of 150 r / min to 200 r / min, a particle size of 200 mesh to 300 mesh, and a hardness of K grade.

10. A graphite silicon carbide composite bearing, characterized in that: A graphite silicon carbide composite bearing prepared by the preparation method according to any one of claims 1 to 9, with a density of 2.5 to 3.2 g / cm 3 ; Thermal conductivity 140~170W / m·k; Flexural strength 190~320MPa; Compressive strength 350~420 MPa.